2021
DOI: 10.1063/5.0063939
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the self-reconstruction ability of the degree of coherence of a light beam via manipulating the cross-phase structure

Abstract: The degree of coherence function of a light beam could be used for optical encryption, robust optical imaging, and other purposes. However, recent works demonstrated that it has a puny self-reconstruction ability that gets worse as the obstacle is further away from the source. In this manuscript, we propose a method by which, with the help of only the introduction of a cross-phase structure in the degree of coherence function, the self-reconstruction ability of the degree of coherence function could be signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…On the other hand, propagation-invariant Airy beams, innately yield a tenfold and fourfold increase in FOV compared to the single-photon Gaussian and Bessel beam light sheets, respectively, while maintaining the high resolution [208,209]. It is also found that the self-healing process is fast in the case of a weak turbid medium, a small size beam width, and low initial coherence, as such this can be used to improve the image quality in a ghost imaging system in a turbid medium (figure 14(d)) [184,210].…”
Section: Microscopy and Imagingmentioning
confidence: 92%
See 1 more Smart Citation
“…On the other hand, propagation-invariant Airy beams, innately yield a tenfold and fourfold increase in FOV compared to the single-photon Gaussian and Bessel beam light sheets, respectively, while maintaining the high resolution [208,209]. It is also found that the self-healing process is fast in the case of a weak turbid medium, a small size beam width, and low initial coherence, as such this can be used to improve the image quality in a ghost imaging system in a turbid medium (figure 14(d)) [184,210].…”
Section: Microscopy and Imagingmentioning
confidence: 92%
“…It is also found that the self-healing process is fast in the case of a weak turbid medium, a small size beam width, and low initial coherence, as such this can be used to improve the image quality in a ghost imaging system in a turbid medium (Fig. 14(d)) [199,203].…”
Section: Microscopy and Imagingmentioning
confidence: 98%
“…Additionally, by utilizing the cross phase, the beam can be rotated during propagation, autofocusing can be performed flexibly, the z-coherence can be enhanced, beam polygonal shaping can be executed, and the beam scintillation of the turbulent disturbance can be mitigated [25][26][27][28][29][30][31]. The cross-phase provides the partially coherent beam with the ability to shape distortions that may occur owing to optical diffraction and obstacles, facilitating robust far-field optical imaging [32][33][34]. However, the present research efforts primarily focus on using cross-phase to manipulate electric fields, intensity, optical coherence, etc., and have not yet used it to carry out phase control of the beam itself.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the partially coherent beam with a special design has also been shown to be self-healing in intensity correlation [27]. The polarization, degree of coherence function, and phase information can also obtain from the defective optical field [28][29][30].…”
Section: Introductionmentioning
confidence: 99%